The Role of Classification Societies in Ensuring MARPOL Compliance (Collaborate Engineering Daily Book Series, 2024)
This study investigates the essential role of classification societies in ensuring compliance with MARPOL regulations to prevent marine pollution. Utilizing a mixed-method approach, data were collected over 18 months from 830 vessels, surveys with 450 maritime professionals, and in-depth interviews with 30 industry experts. Findings show that vessels under regular classification society oversight exhibited substantial reductions in violations, particularly in air emissions (42.3%), ballast water management (38.7%), and oil pollution prevention (33.2%). Furthermore, vessels receiving consistent technical support maintained compliance rates 2.3 times higher than those with minimal support (95% CI: 1.8-2.8). Digital transformation initiatives enhanced response times to potential violations by 67.3% and lowered inspection costs by 42.5%, while improved stakeholder collaboration reduced compliance disputes by 43.2% and increased voluntary compliance initiatives by 52.6%. Despite these advances, challenges remain, particularly in resource allocation for smaller ports and the evaluation of new environmental technologies. This research underscores the importance of further investment in digital infrastructure, capacity-building programs, and international collaboration to strengthen sustainable shipping practices. These findings provide valuable insights for policy development and industry improvements in maritime environmental compliance.
Keywords: MARPOL compliance, classification societies, maritime environmental protection, digital transformation, stakeholder collaboration, sustainable shipping